All‐inside single‐bundle and modified double‐bundle anterior cruciate ligament reconstruction techniques guarantee stability and similar clinical results at over 5 year follow‐up - Lorenzo Moretti; Raffaele Garofalo; Giuseppe Danilo Cassano; Roberto Calbi; Francesco Fiore; Giuseppe Solarino (Journal of Experimental Orthopaedics)
Abstract Purpose The aim of the present study was to compare clinical and radiological outcomes between the all‐inside single bundle (SB) and a modified double‐bundle (DB) anterior cruciate ligament reconstructions (ACLR) at over 5‐year follow‐up. Methods This is an observational, retrospective comparative, two‐centre study. Clinical outcomes were evaluated using Lysholm and International Knee Documentation Committee (IKDC) scores, and anterior tibial translation (ATT) was assessed using the KT‐1000 arthrometer. Knee x‐ray images were recorded, classified according to the KL grading and compared with radiographs of the same patient before surgery. Inclusion criteria were patients undergoing ACLR, age between 18 and 45 years and negative knee history of major traumatic events after surgery. Exclusion criteria were congenital laxity, combined multiple knee ligament injuries, patients undergoing ACL revision surgery, history of infection, lower limb coronal axial deviation >5°, patients undergoing lateral extra‐articular tenodesis or anterolateral ligament reconstruction, patients with chondral damage Outerbridge grade >2, patients with meniscal tears undergoing subtotal meniscectomy or meniscal repair and patients with knee OA Kellgren–Lawrance (KL) grade >3. Results One hundred and fifty‐two patients were included in the study. Patients were divided into two groups according to surgical technique: Group A—ACLR with all‐inside technique, and Group B—ACLR with modified DB technique. There were no statistical differences between groups for age, side, gender or time since surgery. There were no statistically significant differences between groups for Lysholm scores (p = 0.43), IKDC (p = 0.88), ATT (p = 0.105) and KL grade (p = 0.93 before surgery, 0.99 at the fu). KL grade increased significantly since pre‐op. Conclusions Our data show significant improvements in all clinical outcome measures, along with excellent KT‐1000 arthrometer values and low clinical failure rates for both the SB all‐inside and modified DB techniques at a mean follow‐up of over 6 years. There were no significant differences in arthritic progression according to KL grade between groups. Level of Evidence Level III.